2015
DOI: 10.1093/jnci/djv301
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Risk of Heart Failure Associated With Adjuvant Trastuzumab in Breast Cancer Patients: A Population Study

Abstract: Adjuvant trastuzumab was associated with increased risk of new incidence of HF in breast cancer survivors during the period of adjuvant treatment but not thereafter. Routine intensive monitoring may not be necessary after completing adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 40 publications
3
60
1
2
Order By: Relevance
“…Contrary to previous studies that investigated the time of occurrence of CHF, which showed that most cardiotoxicities occurred within the first year after an anthracycline chemotherapeutic regimen, the rates of CHF continued to increase throughout this study . This could have been caused by the difference in the anthracycline dose.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…Contrary to previous studies that investigated the time of occurrence of CHF, which showed that most cardiotoxicities occurred within the first year after an anthracycline chemotherapeutic regimen, the rates of CHF continued to increase throughout this study . This could have been caused by the difference in the anthracycline dose.…”
Section: Discussioncontrasting
confidence: 98%
“…In terms of trastuzumab, our results showed results similar to those of a previous study . One study reported that the effect of trastuzumab was not associated with long‐term CHF in breast cancer survivors …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Conditional mutant mice carrying a cardiac-restricted deletion of ErbB2 (HER-2) developed cardiac chamber dilation, wall thickening, and decreased contractility (Crone et al , 2002; Ozcelik et al , 2002). Patients who have been developing cardiotoxicity while receiving trastuzumab generally improved on removal of the agent (Goldhar et al , 2015). Lapatinib seemed to be associated with lower risk but none of the trials has directly compared trastuzumab and lapatinib (Johnston et al , 2009; Blackwell et al , 2010).…”
Section: Discussionmentioning
confidence: 99%